IMPLEMENTASI UU NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DI KABUPATEN MAMBERAMO TENGAH TAHUN 2019 - Atius Karoba; Nur Aedah (Universitas Cenderawasih, 2022)
The purpose of this study is to determine and analyze the implementation of the policy of Law Number 7 of 2017 concerning the General Election of the Regional People's Representative Council (DPRD) in Central Mamberamo Regency. This study uses a qualitative method. Data collection techniques using interviews and observation. From the results and discussion of this research, that the results of the legislative elections there are those who feel dissatisfied with the performance of the General Election Commission of Central Mamberamo Regency, after the implementation of the stages but with some requirements for improvement still must be improved in the performance of the General Election Commission. Furthermore, the service as a member of the General Election Commission also participates in hearing input or instructions by the regional head which is the work target of the General Election Commission of Central Mamberamo Regency. In the previous year and until the 2019 legislative general election, the performance of the general election commission was unprofessional in the attention of the people of Central Mamberamo Regency, with the results of the work or policies and decisions of the General Election Commission resulting in conflicts in the region.